Production of Lipase by Isolated Halophile, Halobacillus sp. Strain AR11 from International Miankaleh Wetland - Sedigheh Rajaei-Maleki; Bagher Seyedalipour; Salman Ahmady-Asbchin; Gholamhossein Riazi (Journal of Genetic Resources, 2021)
Lipases are particularly important because they specifically hydrolyze acyl glycerol, oils, which are of great interest for different industrial applications. Some halophilic microorganisms produced some lipases. Halophilic bacteria have greater ability to produce salt and thermo tolerant enzymes like amylases, proteases and lipases. Most industrial enzymatic functions may be stopped by concentrated salt solutions and high temperatures; therefore, halophilic enzymes that have optimal activity at a vast range of temperature, pH and ionic strength, would be considered as suitable biocatalysts in industrial processes. The aim of this study was to isolate and study the halophilic lipase producing bacteria from the Miankaleh Wetland. The lipase activity was measured using titrimetric methods. Three halophilic strains (AR11, AR18 and AR28) were isolated from the Miankaleh wetland and were screened for the production of hydrolytic enzymes and lipolytic activity. Among three isolates, one strain was selected for identification using the molecular methods and some morphological characteristics. The bacterium Halobacillus truperi AR11 with 1.82 ± 0.1 U/mL lipase activity was selected as the highest lipase producing isolate. Lipase enzyme produced by this potential isolate was also characterized for determining its optimal activity. Effect of different pH, NaCl concentration and temperature on lipase activity was determined. The optimum pH for AR11 was found to be 9, while the optimum temperature and NaCl concentration for lipase activity was found to be 45ºC and 5 % NaCl, respectively. This is the first report of isolation and molecular identification of lipase producing halophilic bacteria from the Miankaleh wetland.